Comparison of machine learning techniques to predict cardiovascular disease - Jaber, Mir Mohammad; Raad, Tahmid Imam; Tasneem, Tasfia (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.